A Woman's Calling (London : National Association of Local Government Officers)
1937 1937 1930s 13 pages FOREWORD In the year 1934, the National Association of Local Government Officers published recommendations relating to nurses and institutional officers. These recommendations were based upon the Report of the “Lancet” Commission, and upon the standards established by the College of Nursing, and the Association has since been engaged in formulating a comprehensive recruitment and training scheme for women engaged in the Public Health Services. The Scheme is now submitted in the hope that it will find favour amongst those engaged in public health work and be generally acceptable to local authorities. The Public Health Services were never more important than they are to-day ; they are varied in the sense that they range from pre-natal advice to providing comfort and consolation to the aged, and they are interrelated all along the line. It’s a woman’s work and it offers all the scope of a great and satisfying career. The conception behind this scheme is the career service, and not just a job. That ideal is only made possible by linking up the various occupations in the hospital and the Public Health Department. It is dependent upon and deserves the goodwill and sympathy of the local authorities into whose care the public health of the nation has been entrusted by Parliament. This Scheme is a women public health workers’ Charter ; it should give hope to the girl whose education and disposition fit her for the hospital and health services, it should persuade authorities to bring organization and vision into their employment of youth. N.A.L.G.O. is prepared to help by offering scholarships and grants to make it possible for talent to transfer from grade to grade and to undertake progressive training. Given adequate facilities and encouragement for training and promotion, the best starting point for practically all the higher posts open to women in the public health field is either the junior clerical posts or probationer nursing. 1 292/54.73/2/1